The Effectiveness of Environmental, Social, and Governance (ESG) Disclosure on Investor Preferences - Ajiani, Ika Putri Fitri; Khairunnisa (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The phenomenon of increasing investor attention to sustainability issues encourages companies to pay attention to the quality of Environmental, Social, and Governance (ESG) disclosures in financial reports. However, there are still differences in the level of ESG disclosure completeness across companies, making it important to examine how this affects investor preferences. This study aims to test the effectiveness of ESG disclosure on investor preferences by comparing three treatment groups: reports with complete, partial, and minimal disclosure. The research method used is a between- subject experimental design with 180 respondents randomly divided into three groups (60 respondents each). Data were analyzed using one-way ANOVA, followed by Post-Hoc Tukey HSD and Independent Sample T-Test to identify differences among groups. The results show significant differences in investor preferences across the three groups, with the order of preference being Group A (Complete) > Group B (Partial) > Group C (Minimal). Complete ESG disclosure significantly increases investor preferences compared to partial or minimal disclosure. The implication of this study is that completeness and transparency of ESG information are not merely a form of regulatory compliance but also a crucial strategy to enhance investor trust, strengthen corporate reputation, and support long-term sustainability in the capital market.